2009
DOI: 10.5194/npg-16-579-2009
|View full text |Cite
|
Sign up to set email alerts
|

Multiscaling analysis of high resolution space-time lidar-rainfall

Abstract: Abstract. In this study, we report results from scaling analysis of 2.5 m spatial and 1 s temporal resolution lidar-rainfall data. The high resolution spatial and temporal data from the same observing system allows us to investigate the variability of rainfall at very small scales ranging from few meters to ∼1 km in space and few seconds to ∼30 min in time. The results suggest multiscaling behaviour in the lidar-rainfall with the scaling regime extending down to the resolution of the data. The results also ind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(26 citation statements)
references
References 22 publications
1
25
0
Order By: Relevance
“…The UM parameter estimates are slightly different with especially a C1 smaller than the ones usually reported at coarser resolution ( ~ 1.7-1.9, C1 ~ 0.05-0.2) by authors who studied rainfall field in space (Mandapaka et al 2009, Verrier et al 2010, Gires et al 2013. Although these authors studied rainfall fields horizontally which makes direct comparison harder (due to a possible anisotropy between the vertical and horizontal directions), this hints at a possible break between two scaling regimes, a small scales one and a large scales one, located at few tens of meters or few hundreds of meters.…”
Section: 2) Scaling Behaviourmentioning
confidence: 87%
See 1 more Smart Citation
“…The UM parameter estimates are slightly different with especially a C1 smaller than the ones usually reported at coarser resolution ( ~ 1.7-1.9, C1 ~ 0.05-0.2) by authors who studied rainfall field in space (Mandapaka et al 2009, Verrier et al 2010, Gires et al 2013. Although these authors studied rainfall fields horizontally which makes direct comparison harder (due to a possible anisotropy between the vertical and horizontal directions), this hints at a possible break between two scaling regimes, a small scales one and a large scales one, located at few tens of meters or few hundreds of meters.…”
Section: 2) Scaling Behaviourmentioning
confidence: 87%
“…Very few studies have analysed this, mainly because of the lack of rainfall data at these scales. Mandapaka et al (2009) observed on lidar data scaling on the range 1 -512 s in time and 2.5 -320 m in space. Lilley et al (2006) and Lovejoy and Schertzer (2008), using few 3D snapshots of an 8 m 3 volume with most of its drops (Desaulnier-Soucy et al 2001), reported a scaling behaviour down to few tens of cm with a dependency on the turbulence intensity and drop size.…”
Section: ) Introductionmentioning
confidence: 99%
“…The choice of such a high value of α is theoretically motivated to better assess the estimate bias resulting from the thresholding and corresponds to an upper bound of empirical estimates on portions of time series or maps where there are (almost) no zeros. For example, de Montera et al (2010) reported C 1 = 0.13 and α = 1.7 for a 30 s time series, Mandapaka et al (2009) reported C 1 = 0.18 and α = 1.9 for spatial and temporal analysis performed on high-resolution (2.5 m, 1 s) lidar data, and Verrier et al (2010) reported C 1 = 0.12 and α = 1.78 for spatial analysis of radar data (1 km resolution). Concerning the additional parameters introduced in the new model, γ 0 =0.1 and p 0 = 0.5 are tested in this section.…”
Section: Results Of Um + 0 For a Set Of Parametersmentioning
confidence: 99%
“…Considering the high spatial variability of rainfall on small scales (e.g. Gires et al, 2014;Jaffrain and Berne, 2012b;Mandapaka et al, 2009), one important challenge of the method becomes obvious here. The section bounds are located at s 3 − s and s 3 + s on both sides of R 3 .…”
Section: Theoretical Frameworkmentioning
confidence: 99%